Hubungan Intensitas Penggunaan Media Sosial Dengan Kecenderungan Body Shaming Pada Remaja Di SMK X - Mita Wijayanti; Fx. Wahyu Widiantoro; Amin Al Adib (Jurnal Psikologi, 2025)
This study aims to examine the relationship between the intensity of social media use and the tendency for body shaming among teenagers at Vocational School physically yourself or others. This research uses a quantitative method with a purposive sampling technique. The sample for this research was 86 students of SMK X. The research instruments used were a social media usage intensity scale and a body shaming tendency scale which had been tested for validity and reliability. The results of data analysis show that there is a positive and significant relationship between the intensity of social media use and the tendency for body shaming among teenagers at SMK X (r= 0.446). This means that the higher the intensity of social media use, the higher the tendency for body shaming, and vice versa.